Investigation on fatigue crack growth in offshore pipelines with internal pressure - Ng, Yue Xing (2017)
Fatigue crack growth is one of the common causes of offshore pipeline failure. Failure of offshore pipeline may lead to catastrophic consequences. Hence, fatigue life prediction is of paramount importance in ensuring the structural reliability of offshore pipeline. There are a broad number of studies on fatigue crack growth of pipeline. However, fatigue study on the interaction of multiple cracks in a pipeline subjected to internal pressure and cyclic loading is not common. A full scale fatigue experiment is too costly and impractical to carry out. In the current project, extended finite element method (XFEM) is adopted for numerical simulations. Coplanar and non-coplanar surface cracks located in the internal and external surfaces of the pipeline have been considered. The influence of different crack geometries and stress ratio on fatigue crack growth and crack interaction are investigated in details. The obtained results on interacting fatigue crack propagation can be used for future pipe design and fatigue crack assessment.